2003
DOI: 10.1021/bm030046v
|View full text |Cite
|
Sign up to set email alerts
|

ATRP Grafting from Cellulose Fibers to Create Block-Copolymer Grafts

Abstract: Cellulose fibers, in the form of a conventional filter paper, have been modified by reacting the hydroxyl groups on the fiber surface with 2-bromoisobutyryl bromide, followed by grafting using ATRP conditions. The papers were first grafted with methyl acrylate (MA), rendering the paper very hydrophobic as reported in an earlier work. The papers were analyzed by gravimetry, FT-IR, ESCA, and AFM. To verify that the polymerization from the surface was "living", a second layer of another, hydrophilic, polymer, 2-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(235 citation statements)
references
References 40 publications
7
228
0
Order By: Relevance
“…This has received much less attention than the alternative approach of grafting onto the surface of solid cellulosic materials (selected 6" " relevant references are cited here 37,38,39 ). The review is arranged into sections based on the parent cellulose derivative undergoing chemical modification.…”
Section: " "mentioning
confidence: 99%
“…This has received much less attention than the alternative approach of grafting onto the surface of solid cellulosic materials (selected 6" " relevant references are cited here 37,38,39 ). The review is arranged into sections based on the parent cellulose derivative undergoing chemical modification.…”
Section: " "mentioning
confidence: 99%
“…10,11,12 Cellulosic fibers meet this need because they possess desirable intrinsic characteristics, such as low cost and density, specific resistance and high elastic modulus, and resistance to compression (or flattening); they are also rigid, non-abrasive, and non-toxic; are easily modified by chemical agents; and are entirely renewable, being the most abundant organic compound on the planet. 2,5,13,14 Considering the positive properties of cellulosic fibers and their potential to improve the mechanical properties of materials used in dentistry, here, we incorporate mechanically processed cellulose fibers into conventional restorative glass ionomer cement (GIC). We evaluate the parameters of the modified GIC, namely, the compressive strength, elastic modulus, and diametral tensile strength and stiffness, and characterize the materials by scanning electron microscopy and energy dispersive X-ray spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity index of fiber, fiber initiator, and fiber-g-PSPMA were 67.55%, 62.41%, and 61.83%, respectively. This indicated that the graft reaction occurred only at the surface of the fiber, and the structure of filter paper was not damaged during the reaction (Carlmark and Malmström 2003). …”
Section: X-ray Scatteringmentioning
confidence: 89%
“…Hence, polymerization reaction carried out both from the surface of fibers and the reaction system, which were triggered from fiber initiator and the sacrificial initiator. This method also used to assess the polymer grafted on the fiber surface (Carlmark and Malmström 2003). The grafted PSPMA were analyzed by GPC and the main result is listed in Table 2.…”
Section: Analysis Of Pspmamentioning
confidence: 99%